Flow cytometry sex sorting affects bull sperm longevity and compromises their capacity to bind to oviductal cells - Carvalho, Jose de Oliveira; Sartori, Roberto; Rodello, Leandro [UNESP]; Mourao, Gerson Barreto; Bicudo, Sony Dimas [UNESP]; Dode, Margot A. N. (Elsevier B.V., 2018)
This study assessed the effect of flow cytometry sexing on sperm longevity and the capacity of sperm to bind to oviductal cells. Each ejaculate from four bulls was divided into two fractions: the first was immediately frozen as non sexed sperm (NS) and the second was sexed originating X- and Y-bearing sperm. The fourth treatment had sex-sorted X and Y sperm (XY) combined. Sperm from each group was assessed for sperm characteristics after thawing, after washing and at 2, 4, 8 and 12 h of incubation at 39 degrees C in 5% CO2 in air. For the binding test, sperm were incubated in sp-TALP medium for 30 min or 24 h with oviductal explants. Percentages of motility (58.1 +/- 4.3 and 35.2 +/- 4.4), progressive motility (46.1 +/- 6.1 and 25.7 +/- 4.8), mitochondrial membrane potential (79.2 +/- 8.3 and 69.0 +/- 6.3), plasma membrane stability (77.4 +/- 4.6 and 19.4 +/- 4.2), and live sperm with intact acrosome (57.2 +/- 8.5 and 31.3 +/- 7.9) were higher in NS than in XY, respectively (P < 0.05). Those differences were maintained for up to 8 h. The sexing process did not affect the sperm binding to the explants after 30 min. However, after 24 h, XY had less (6.7 +/- 2.0) sperm bound to explants than NS (23.6 +/- 7.2). In conclusion, even though XY was of lower quality than NS, the decreases in quality in both NS and XY groups were similar between groups during incubation. Moreover, the sex-sorting process affected the ability of sperm to remain bound to oviductal explants.
Keywords: Bovine; Capacitation; Oviduct; Sperm reservoir; Maternal communication